Prevalence and Factors Associated with Interpersonal Violence among In-School Adolescents in Ghana: Analysis of the Global School-Based Health Survey Data - Richard Gyan Aboagye; Abdul-Aziz Seidu; Francis Arthur-Holmes; James Boadu Frimpong; John Elvis Hagan; Hubert Amu; Bright Opoku Ahinkorah (MDPI AG, 2021)
Interpersonal violence is a critical public health concern that is linked with many negative consequences, including mortality. It is the second most predominant cause of death among male adolescents aged 15-19. This study used a nationally representative data from the recent Ghana Global School-based Health Survey to examine the prevalence and factors associated with interpersonal violence among Ghanaian in-school adolescents. A total of 2214 in-school adolescents were included in the final analysis. Multivariable binomial logistic regression analysis was performed to determine the factors assciated with interpersonal violence. The results of the regression analysis were presented as adjusted odds ratios (aOR) with 95% confidence level (CI) in all the analyses. Statistical significance was set at p < 0.05. The overall prevalence of interpersonal violence was 55.7%, of which the prevalences of physical fighting and attack were 38.2% and 41.5%, respectively. In-school adolescents who had an injury were more likely to experience interpersonal violence (aOR = 2.29, 95% CI = 1.71-3.06) compared with those who did not have an injury. The odds of interpersonal violence were higher among in-school adolescents who were bullied (aOR = 2.48, 95% CI = 1.84-3.34) compared with those who were not bullied. In addition, in-school adolescents who attempted suicide (aOR = 1.56, 95% CI = 1.22-2.47), consumed alcohol at the time of the survey (aOR = 1.88, 95% CI = 1.15-3.06), and were truant (aOR = 1.58, 95% CI = 1.29-1.99) had higher odds of experiencing interpersonal violence. These factors provide education directors and school heads/teachers with the relevant information to guide them in designing specific interventions to prevent interpersonal violence, particularly physical fights and attacks in the school settings. School authorities should organize parent-teacher meetings or programs to help parents improve their relationships with in-school adolescents to prevent or minimize their risky behaviors, including physical fights.